An Anesthesia Preinduction Checklist to Improve Information Exchange, Knowledge of Critical Information, Perception of Safety, and Possibly Perception of Teamwork in Anesthesia Teams. Issue 4 (August 2016) - Tscholl, David W.; Weiss, Mona; Kolbe, Michaela; Staender, Sven; Seifert, Burkhardt; Landert, Daniel; Grande, Bastian; Spahn, Donat R.; Noethiger, Christoph B.
Abstract : (Abstracted from Anesth Analg, 121:948–956, 2015) The World Health Organization (WHO) surgical safety checklist contains only a few supercritical anesthesia items. Consequently, the authors of the current study assess a separate anesthesia preinduction checklist (APIC), meant to complement the WHO checklist and improve 5 team-level outcomes (information exchange, knowledge of critical information, team members' perception of safety and teamwork, and clinical performance).